Rare bird documentation form for Greater Scaup at Big Creek State Park, 1987 - Dinsmore, Stephen J.et al (1987)
Rare bird documentation form for two Greater Scaups at Big Creek State park in Polk County, IA on October 5, 1987. Epson - sheet feed